FOOD SAFETY EDUCATION FROM LEAFLET-BASED PLASTIC AND STYROFOAM PACKAGING - Asri Jumadewi; Orisinal Orisinal; Erlinawati Erlinawati (Serambi Journal of Agricultural Technology, 2022)
Abstract This study aims to determine the knowledge and attitudes of the community towards food safety from the use of plastic and styrofoam as packaging. Plastic and styrofoam are food packaging that contain monomers and additives in the form of plasticizers. These monomers can migrate into packaged foods. This will reduce the quality of food due to exposure to materials. These movable plastic and styrofoam materials can be carcinogenic and hazardous to health. This research was conducted in Lamujong Village, Baitussalam Aceh Besar, using a purposive sampling technique to obtain 32 respondents. This research was conducted from 15 to 20 August 2022. The research method is a descriptive method in the form of educating the public by conducting observations and interviews using leaflets. Based on the results of the study, it showed that there was an increase in respondents' knowledge and attitudes about the use of plastic and styrofoam packaging in order to become food safety for packaged food.